Arguedas y los encuentros culturales de Miguel Giusti, Cecilia Esparza, Gabriela Núñez, Carmen Pinilla, Gonzalo Portocarrero, Cecilia Rivera, Eileen Rizo-Patrón, Carla Sagástegui (Editores) - Pinilla, Carmen María (2013)
No presenta resumen.